Unraveling the modulatory manner and function of circRNAs in the Asian honey bee larval guts - Gao, Xuze; Zang, He; Liu, Xiaoyu; Guo, Sijia; Ye, Daoyou; Liu, Zhitan; Jing, Xin; Niu, Qingsheng; Wu, Ying; Lü, Yang; Chen, Dafu; Guo, Rui (Frontiers in Cell and Developmental Biology, 2024)
Circular RNAs (circRNAs) are a class of non-coding RNAs (ncRNAs) that can participate in biological processes such as gene expression, growth, and development. However, little has been explored about the function of circRNAs in the development of Apis cerana larval guts. By using our previously gained deep sequencing data from the guts of A. cerana worker larvae at 4-, 5-, and 6-day-old (Ac4, Ac5, and Ac6 groups), the expression pattern and regulatory role of circular RNAs (circRNAs) during the development process was comprehensively investigated, with a focus on differentially expressed circRNAs (DEcircRNAs) relevant to immunity pathways and developmental signaling pathways, followed by validation of the binding relationships among a key competing endogenous RNA (ceRNA) axis. Here, 224 (158) DEcircRNAs were detected in the Ac4 vs. Ac5 (Ac5 vs. Ac6) comparison group. It’s suggested that 172 (123) parental genes of DEcircRNAs were involved in 26 (20) GO terms such as developmental process and metabolic process and 138 (136) KEGG pathways like Hippo and Wnt signaling pathways. Additionally, ceRNA network analysis indicated that 21 (11) DEcircRNAs could target seven (three) DEmiRNAs, further targeting 324 (198) DEmRNAs. These DEmRNAs can be annotated to 33 (26) GO terms and 168 (200) KEGG pathways, including 12 (16) cellular and humoral immune pathways (endocytosis, lysosome, Jak-STAT, etc.) and 10 (nine) developmental signaling pathways (Hippo, mTOR, Hedgehog, etc.). Interestingly, DEcircRNAs in these two comparison groups could target the same ace-miR-6001-y, forming complex sub-networks. The results of PCR and Sanger sequencing confirmed the back-splicing sites within four randomly selected DEcircRNAs. RT-qPCR detection of these four DEcircRNAs verified the reliability of the used transcriptome data. The results of dual-luciferase reporter assay verified the binding relationships between novel_circ_001627 and ace-miR-6001-y and between ace-miR-6001-y and apterous-like. Our data demonstrated that DEcircRNAs were likely to modulate the developmental process of the A. cerana worker larval guts via regulation of parental gene transcription and ceRNA network, and novel_circ_001627/ace-miR-6001-y/apterous-like was a potential regulatory axis in the larval gut development. Findings from this work offer a basis and a candidate ceRNA axis for illustrating the circRNA-modulated mechanisms underlying the A. cerana larval guts.